GEOCHEMICAL FRACTIONATION OF TOXIC TRACE HEAVY METALS (CR, CU, PB, AND ZN) FROM THE ESTUARINE SEDIMENTS OF 5 RIVER MOUTHS AT JAKARTA BAY, INDONESIA - Noverita Dian Takarina (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Jakarta Bay is located at the north coast of Jakarta bordered by 106 03'00'' Longitude and 6 10'30'' Latitude. Administratively bordered by Bekasi Regency on the east and Tangerang Regency on the west. There are  13 -19 rivers flow to the bay with 2050 industries  that produce hazardous waste, including heavy metals. Metal concentrations in surface sediments and their spatial distributions have increased, recently. Concentration of Pb during 10 years period increase from 23.3 mg kg-1 to 118.2 mg kg-1. The objectives of this study is to know the distribution of Chromium (Cr), Copper (Cu), Lead (Pb), and Zinc (Zn) of Jakarta Bay, Indonesia and their geochemical partition in marine sediments that are bound to “Exchangeable Fraction”, “Reducible Fraction”, “Fe-Mn Oxide Fraction”, “Oxidize able Fraction”, and “Residual Fraction”. The result showed that the concentration of heavy metals in the sediments in most locations were above the Canadian Standard for Contaminated sediments. Concentration of Cr ranged from 48.68—292.09 ppm, Cu ranged between 18.62—151.82 ppm, Pb ranged from 39.7—303.42 ppm, and Zn ranged between 165.83—487.69 ppm. Standard for Cr, Cu, Pb, and Zn are 22 ppm, 30 ppm, 25 ppm, and 60 ppm, respectively. Percent fraction of Cr in labile fraction (F1, F2, and F3) ranged from 30-60 %, while for Cu, its percent fraction mostly bound to lithogenic fraction as much as 38–78%.  Percent of labile fraction of Pb ranged from 22-54 %, while for Zn as much as 15-72%.  These meant that not only Cr but also Pb and Zn were possible to be easily released in the environment as bioavailable metals for biota, especially, benthic invertebrates.